The effect of Driver's model on learning the skill of chest handling and peaceful scoring in basketball (Journal of the College of Basic Education, 2024)
Specialists confirm that there is an important element, which is teaching, which is expressed through intentional organization of experiences and leads learners to acquire specific skills that vary from simple memorization of knowledge to mastery and learning higher thinking skills in all educational fields. This leads to the use of modern educational techniques through educational means, tools, techniques and devices. Taking into account the learning and teaching environment and how it is organized and arranged to serve and benefit the educational situation and address important educational problems in a flexible, systematic manner that takes organized, sequential and integrated steps to contribute to creating practical scientific additions for learners to keep pace with the development that has occurred in all scientific fields and achieve specific positive behavioral, pedagogical and educational goals The research objectives included the following1.Preparing special educational units according to Driver’s model to learn the skill of chest handling and the skill of peaceful scoring2.Knowing the impact of educational units using Driver’s modelThe researcher used the experimental method for its suitability and the requirements of the research. The research community was chosen, which is represented by the students of the first stage of Assyria University (Faculty of Physical Education and Sports Sciences) for the academic year (2023-2024), where their number reached (75) students, in addition to the use of, a basketball offensive skills test, Statistical data were extracted and processed using the statistical package (SPSS).The fourth chapter included presenting, analyzing, and discussing the results in a scientific manner to achieve the research objectives and reach scientific results The most important conclusions he reached are 1.The contributions of Driver’s model in learning the skill of chest handling and peaceful scoring in basketball 2.Driver’s model has merit in arranging and organizing the lesson by making it clearer and more organized In light of the conclusions reached by the researcher, he recommends the following 3.Emphasis on employing Driver’s model in physical education lessons because of its effective role in the educational process